Lamellar keratoplasty using acellular porcine corneal stroma for the treatment of corneal ulcers - Hu, Yiming; Zhang, Lan; Wu, Lei; Zhu, Yao; Wu, Li; Li, Chenye; Ruan, Youyang; Hu, Yunwei; Wang, Feifei; Lin, Zhirong; Jin, Qifang (Frontiers in Medicine, 2025)
ObjectiveThe study aimed to investigate the efficacy and safety of acellular porcine corneal stroma (APCS) for lamellar keratoplasty in the treatment of corneal ulcers.MethodsA total of 14 patients (14 eyes) diagnosed with corneal ulcers who underwent lamellar keratoplasty using acellular porcine corneal stroma at the Second Affiliated Hospital of Nanchang University between June 2016 and May 2017 were recruited and followed up for at least 12 months. Postoperative visual acuity, epithelial recovery, graft transparency, the recurrence rate of corneal ulcers, the rate of graft rejection, corneal neovascularization, graft infection, secondary glaucoma, and graft melting were examined and analyzed.ResultsAll 14 patients (100%) who underwent lamellar keratoplasty using acellular porcine corneal stroma successfully preserved the structure of their eyeballs. The visual acuity improved in 11 patients (78.5%). Graft rejection occurred in one patient (7.1%), while two patients (14.3%) developed recurrent corneal ulcers. Corneal vessel ingrowth was observed in seven patients (50%), and one patient (7.1%) developed pseudopterygium. The average time for complete epithelial recovery was 3–7 days.ConclusionLamellar keratoplasty using acellular porcine corneal stroma is an effective surgical alternative for the treatment of corneal ulcers.